Mineral ballast and particle settling rates in the coastal upwelling system off NW Africa and the South Atlantic - G. Fischer; G. Karakas; M. Blaas; V. Ratmeyer; N. Nowald; R. Schlitzer; P. Helmke; R. Davenport; B. Donner; S. Neuer; G. Wefer (International Journal of Earth Sciences, 2009)

Stable oxygen isotopes in Porites corals monitor weekly temperature variations in the northern Gulf of Aqaba, Red Sea - S. Al-Rousan; S. Al-Moghrabi; J. Ptzold; G. Wefer (Coral Reefs, 2003)

Oscillations of the siliceous imprint in the central Benguela Upwelling System from MIS 3 through to the early Holocene: the influence of the Southern Ocean - O. Romero; G. Mollenhauer; R. R. Schneider; G. Wefer (Journal of Quaternary Science, 2003)
Based on a high‐resolution analysis of the diatom signal and biogenic bulk components at site GeoB3606‐1 (25°S, off Namibia), we describe rapid palaeoceanographic changes in the Benguela Upwelling System (BUS) from early MIS 3 through to the early Holocene (55 000 to 7 000 14 C yr BP). Coastal upwelling strongly varied at 25°S from MIS 3 through to MIS 2. The abrupt decrease in the accumulation rate of biogenic silica and diatoms from MIS 3 into MIS 2 records rapid oceanographic changes in the BUS off Namibia. During MIS 3, leakage of excess H 4 SiO 4 acid from the Southern Ocean into low‐latitude surface waters, as indicated by the occurrence of Antarctic diatoms, enhanced the production of spores of Chaetoceros at the expense of calcareous phytoplankton. Furthermore, shallower Antarctic Intermediate Water (AAIW) would have enriched the thermocline off Namibia with silicate transported from the Southern Ocean. The strong decrease of the siliceous signal throughout MIS 2 represents a decrease in the nutrient input to the BUS, even though the diatom assemblage is still dominated by spores of the upwelling‐associated diatom genus Chaetoceros . Depletion of silicate in the thermocline from the onset of MIS 2 through to the early Holocene reflects the shutdown of AAIW injection from the Southern Ocean into the BUS, causing upwelled waters to become reduced in silicate, hence less favourable for diatom production. The deglaciation and early Holocene are characterised by the replacement of the upwelling‐associated flora by a non‐upwelling‐related diatom community, reflecting weakened upwelling, retraction of the seaward extension of the chlorophyll filament off Lüderitz, and dominance of warmer waters. Copyright © 2003 John Wiley & Sons, Ltd.

Mediterranean climate variability during the Holocene - J.S.L. CASFORD; R. ABU-ZIED; E.J. ROHLING; S. COOKE; K.P. BOESSENKOOL; H. BRINKHUIS; C. DE VRIES; G. WEFER; M. GERAGA; G. PAPATHEODOROU; I. CROUDACE; J. THOMSON; et al. (Mediterranean Marine Science, 2001)
We present a study on four high sedimentation-rate marine cores with suppressed bioturbation effects, recovered along the northern margin of the eastern Mediterranean. We demonstrate that this region, central to the development of modern civilisation, was substantially affected throughout the Holocene by a distinct cycle of cooling events on the order of 2o C. In the best-preserved cases the onset of these events appears particularly abrupt, within less than a century. The cooling events typically lasted several centuries, and there are compelling indications that they were associated with increased aridity in the Levantine/NE African sector (Rossignol-Strick, 1995; 1998; Alley et al., 1997; Hassan, 1986; 1996; 1997a,b; McKim Malville et al., 1998). Several of these episodes appear coincident with cultural reorganisations, with indigenous developments (eg. cattle domestication, new technologies) and population migrations and fusion of peoples and ideas (Hassan, 1986; 1996; 1997a,b; McKim Malville, 1998). We infer that climatic events of a likely high-latitude origin (O’Brien et al., 1995; Bond et al., 1997; Mayewski et al., 1997; Alley et al., 1997) caused cooling and aridity in and around the eastern Mediterranean via a direct atmospheric link, and therefore played an important role in the development of modern civilisation.

Mid-Holocene stable isotope record of corals from the northern Red Sea - Y. A. Moustafa; J. Pätzold; Y. Loya; G. Wefer (International Journal of Earth Sciences, 2000)

North Atlantic climate variability since AD 1350 recorded in δ 18 O and skeletal density of Bermuda corals - S. Draschba; J. Pätzold; G. Wefer (International Journal of Earth Sciences, 2000)

Monitoring climate variability over the past 116 years in coral oxygen isotopes from Ningaloo Reef, Western Australia - H. Kuhnert; J. Pätzold; K. -H. Wyrwoll; G. Wefer (International Journal of Earth Sciences, 2000)

Link between the North and South Atlantic during the Heinrich events of the last glacial period - L. Vidal; R.R. Schneider; O. Marchal; T. Bickert; T.F. Stocker; G. Wefer (Climate Dynamics, 1999)

Climatic changes during the last deglaciation recorded in sediment cores from the northeastern Brazilian Continental Margin - H. W. Arz; J. Pätzold; G. Wefer (Geo-Marine Letters, 1999)

A 200-year coral stable oxygen isotope record from a high-latitude reef off Western Australia - H. Kuhnert; J. Pätzold; B. Hatcher; K.-H. Wyrwoll; A. Eisenhauer; L. B. Collins; Z. R. Zhu; G. Wefer (Coral Reefs, 1999)

Spatial variations in euphotic zone nitrate utilization based on δ 15 N in surface sediments - M. E. Holmes; P. J. Müller; R. R. Schneider; M. Segl; G. Wefer (Geo-Marine Letters, 1998)